Kebenaran Penciptaan sebagai Nilai Penting Kehidupan Manusia: Sebuah Telaah Teoologis atas Teks KGK 287 - Setiawan, Krisna (Felicitas, 2021)
Creation is one of the basic dogmas in the teaching of the Catholic Church faith. This faith in creation has an important meaning, especially for the history of salvation that God designed from the beginning. Everything happens in His infinite goodness for all creatures, especially humans. With the grace and encouragement of their nature, humans can recognize the goodness of the Creator and unite with their Creator, namely Allah. In human history, God has revealed himself to mankind so that he is increasingly recognized and loved by his creation.